The Impact of Digital Devices on Children’s Health: A Systematic Literature Review - Valentina Presta; Alessandro Guarnieri; Fabiana Laurenti; Salvatore Mazzei; Maria Luisa Arcari; Prisco Mirandola; Marco Vitale; Michael Yong Hwa Chia; Giancarlo Condello; Giuliana Gobbi (Journal of Functional Morphology and Kinesiology)
Background: The impact of prolonged digital device exposure on physical and mental health in children has been widely investigated by the scientific community. Additionally, the lockdown periods due to the COVID-19 pandemic further exposed children to screen time for e-learning activities. The aim of this systematic review (PROSPERO Registration: CRD42022315596) was to evaluate the effect of digital device exposure on children’s health. The impact of the COVID-19 pandemic was additionally explored to verify the further exposure of children due to the e-learning environment. Methods: Available online databases (PubMed, Google Scholar, Semantic Scholar, BASE, Scopus, Web of Science, and SPORTDiscus) were searched for study selection. The PICO model was followed by including a target population of children aged 2 to 12 years, exposed or not to any type of digital devices, while evaluating changes in both physical and mental health outcomes. The quality assessment was conducted by using the Joanna Briggs Institute (JBI) Critical Appraisal Tool. Synthesis without meta-analysis (SWiM) guidelines were followed to provide data synthesis. Results: Forty studies with a total sample of 75,540 children were included in this systematic review. The study design was mainly cross-sectional (n = 28) and of moderate quality (n = 33). Overall, the quality score was reduced due to recall, selection, and detection biases; blinding procedures influenced the quality score of controlled trials, and outcome validity reduced the quality score of cohort studies. Digital device exposure affected physical activity engagement and adiposity parameters; sleep and behavioral problems emerged in children overexposed to digital devices. Ocular conditions were also reported and associated with higher screen exposure. Home confinement during COVID-19 further increased digital device exposure with additional negative effects. Conclusions: The prolonged use of digital devices has a significant negative impact on children aged 2 to 12, leading to decreased physical activity, sleep disturbances, behavioral issues, lower academic performance, socioemotional challenges, and eye strain, particularly following extended online learning during lockdowns.